The Struggle for Food Sovereignty Alternative Development and the Renewal of Peasant Societies Today - Herrera, Remy; Lau, Kin Chi (Pluto Press, 2015)
The world's food system is broken, and today's peasant societies are at a crossroads. This collection explores the multiplicity of problems faced by global family agricultures in the current neoliberal era. The contributors, including include Samir Amin, Joao Pedro Stedile and Utsa Patnaik, argue that an understanding of the revival of peasant struggles for their social emancipation and legitimate right of access to land is essential. Financialisation is undermining their work, and must be resisted if they are to construct a new, socially just food system. This is a response to the confusion surrounding how these urgent problems are understood, with the authors offering solutions as to how they should be resolved. They express the importance of the co-operation and cohesion of the various struggles taking place across Latin America, Africa, Asia, Oceania and Europe, and how they must share a common vision for the future.